The Commando procedure for pediatric patients: A case seriesCentral MessagePerspective - Hiroo Kinami, MD; David M. Kalfa, MD, PhD; Andrew B. Goldstone, MD, PhD; Mattan I. Setton, MD; Anne Marie Ferris, MD; Emile A. Bacha, MD (JTCVS Techniques)
Objective: The Commando procedure involves division of the intervalvular fibrous body, mitral valve replacement, and aortic valve replacement. It is considered a technically challenging procedure and traditionally has had high mortality. Methods: Five pediatric patients with combined left ventricular inflow and outflow obstruction were included in this study. Results: There were no early or late deaths during follow-up, and no pacemakers were implanted. None of the patients required reoperation during follow-up, and none developed a clinically significant gradient across the mitral valve or aortic valve. Conclusions: The risks of this operation for patients with congenital heart disease undergoing multiple redo operations should be weighed against the benefits of normal-size mitral and aortic annular diameters and dramatically improved hemodynamics.